CERITA PANJI DALAM PERSPEKTIF SEJARAH - Budiyono, Sunu Catur (LPPM Universitas PGRI Adi Buana Surabaya, 2018)
As a story which spread is dominated by oral tradition, Panji is presented in various versions. Meanwhile,history uses facts, data, or documents to be systematically explored and elaborated. In this case, history speaks in thedomain of